Towards the Preparation of Strategic Plan for Teacher Education Programs - Digo, Gerry S. (ASEAN Journal of Education, 2023)
This paper presents the six-year strategic plan for the teacher education programs of a state college in the Province of Sorsogon, Philippines. Convergent mixed methods using content analysis and survey design which were triangulated with small group discussion were used. The survey was participated by 100 respondents identified through convenience sampling. The strategic planning and management process was adapted in the preparation of the plan. The highlights of this paper include the presentation of the key result areas for each objective of the teacher education programs, benchmark performance and performance targets, strengths, weaknesses, opportunities and threats, and the proposed strategies, programs, activities, tasks and resources. Program differentiation with other teacher education institutions was targeted through capacity development, curriculum leadership, productivity improvement, and quality management. Hence, a strategic plan for the teacher education programs was prepared that serves as a guide for the annual educational programming, implementation, and evaluation to transform the program as the Center of Excellence for Teacher Education by 2020. It is recommended that the annual performance reviews for the teacher education programs of the state college are conducted along with the benchmarks and targets established for the program in this strategic plan together with the implementation of the adjustments whenever necessary.